2019
DOI: 10.1370/afm.2336
|View full text |Cite
|
Sign up to set email alerts
|

Managing Antidepressant Discontinuation: A Systematic Review

Abstract: PURPOSE We aimed to determine the effectiveness of interventions to manage antidepressant discontinuation, and the outcomes for patients. METHODSWe conducted a systematic review with narrative synthesis and meta-analysis of studies published to March 2017. Studies were eligible for inclusion if they were randomized controlled trials, quasi-experimental studies, or observational studies assessing interventions to facilitate discontinuation of antidepressants for depression in adults. Our primary outcomes were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 49 publications
(81 reference statements)
3
62
0
Order By: Relevance
“…In the quantitative systematic review (see ref. 25 for full results), a variety of therapeutic techniques were implemented including a patient-specific letter to the GP with a recommendation to discontinue plus tapering advice; GP review of the patient’s condition and medication; CBT plus tapering; MBCT with tapering support gradual discontinuation and 1-week tapering. The results indicated that CBT or MBCT plus tapering are helpful for patients discontinuing antidepressants, with cessation rates of 40%–95%,23 compared with only 6%–8% cessation where health professionals are simply prompted to review patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the quantitative systematic review (see ref. 25 for full results), a variety of therapeutic techniques were implemented including a patient-specific letter to the GP with a recommendation to discontinue plus tapering advice; GP review of the patient’s condition and medication; CBT plus tapering; MBCT with tapering support gradual discontinuation and 1-week tapering. The results indicated that CBT or MBCT plus tapering are helpful for patients discontinuing antidepressants, with cessation rates of 40%–95%,23 compared with only 6%–8% cessation where health professionals are simply prompted to review patients.…”
Section: Resultsmentioning
confidence: 99%
“…Two systematic reviews were conducted: a quantitative review with meta-analysis, and a qualitative thematic synthesis, described in detail elsewhere 10 25…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, discontinuation can cause a group of symptoms that are very unpleasant and can lead patients to continue to seek the medications. 5,8,10,[13][14][15] The persistent use is not for a high but to alleviate symptoms of disease or to avoid unpleasant ADSs.…”
Section: Antidepressant Discontinuation Syndromementioning
confidence: 99%
“…Kendrick and a UK team reviewed studies on the care of adults with depression and conclude that risk of recurrence may be lessened with slow tapering of antidepressants and cognitive behavioral therapy. 1 In screening for depression and anxiety disorders in primary care, Graham and team show that a computerized adaptive test performed similarly to clinical interview and paper-and-pencil tests. Such technology might help screen more patients for these important problems and free up time for clinicians to spend more face-to-face time with patients.…”
mentioning
confidence: 99%